2011
DOI: 10.1111/j.1365-2621.2011.02724.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, resistant starch content and enzymatic digestibility of unripe banana, edible canna, taro flours and their rice noodle products

Abstract: Unripe banana, edible canna and taro flours, which have been reported to contain significant amounts of fibre, were investigated for their physicochemical properties, resistant starch (RS) content and in vitro starch digestibility, and compared with commercial high-fibre-modified starches from corn and tapioca. Differential scanning calorimetry showed a single endothermic peak located around 70-83°C for the samples except the modified starches, which exhibited no transition enthalpy. The samples showed differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The present study showed that native S. grossus flour and starch can have the potential of being used as functional food ingredients for low GI foods. This appears to support the conclusions of Moorthy (2002) and Srikaeo et al (2011) that some tropical tuber and root crop starches have the potential to be used in low GI foods. Comparing among all samples, S. grossus starch has higher digestion rate than those of the flours.…”
Section: Dscsupporting
confidence: 85%
“…The present study showed that native S. grossus flour and starch can have the potential of being used as functional food ingredients for low GI foods. This appears to support the conclusions of Moorthy (2002) and Srikaeo et al (2011) that some tropical tuber and root crop starches have the potential to be used in low GI foods. Comparing among all samples, S. grossus starch has higher digestion rate than those of the flours.…”
Section: Dscsupporting
confidence: 85%
“…According to Ovando‐Martinez et al. (), Trinidad, Mallillin, Loyola, Sagum, and Encabo (), and Srikaeo, Sukanya, and Sopade (), unripe banana and legumes such as cowpea and pigeon pea are good sources of dietary fiber (21–41 g/100 g sample) and can be used in the preparation of functional foods. The recommended daily intake of dietary fiber for a healthy adult is 20–25 g (Dhingra, Michael, Rajput, & Patil, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, much less information is available regarding rice noodles, perhaps due to the more severe effect of DF on their textural qualities. According to the report of Srikaeo, Mingyai, and Sopade (2011), noodles made from rice flour replaced with 20% unripe banana flour, canna flour or commercial modified corn starch had significantly higher RS content (2.5%, 3.6% and 8.8%, respectively) than noodles made from rice flour only (1.0%). Recently, Wandee et al (2014) showed that rice noodles incorporated with 15% cassava pulp and 5% pomelo peel contained much higher total dietary fiber (TDF) content (14.4%) than the control (3.0%), while their textural properties were comparable.…”
Section: Introductionmentioning
confidence: 95%